Persepsi Mahasiswa Terhadap Penggunaan Ruang Terbuka Hijau Di Universitas Negeri Jakarta Ditinjau Dari Fungsi Ekstrinsik - Irfan Husaini; Henita Rahmayanti (LPPM Universitas Negeri Jakarta, 2015)
This research aim to determine student’s perceptions toward green open space that has been there at the A Campus of State University of Jakarta reviewed from extrinsic functions. The research held at the A Campus of State University of Jakarta on June-July 2015.The method used in this research was a descriptive research method with survey. Sampling population in this research are students which use green open space at the A campus of State University of Jakarta. Target population in this research are students of state university of jakarta which using green open space at crowded hour. Data collection conducted with questionnaire and documentation.Results of this research are students' perceptions of the cultural dimension of the social function of the percentage reached 52.51% at one indicator assume this function has been reached, the dimensions of the aesthetic function is also considered to have achieved the highest percentage of 55.65% in one indicator, while the dimensions of the economic functions of the highest percentage of 46.86% is not considered an indicator of the implementation of this function well